Prevalência de doença arterial obstrutiva periférica (DAOP) e alterações sensoriais em pacientes diabéticos tipo 2: impacto da DAOP sobre a qualidade de vida, nível de atividade física e composição corporal - Sales, Ana Tereza do Nascimento (2012)
Diabetes Mellitus (DM) affected approximately 171 million people in the world in the year 2000 as described by the World Health Organization (WHO). Because DM is a multisystem disease it can cause several complications especially those related to the cardiovascular system. The Peripheral Arterial Disease (PAD) of the lower limbs and the Diabetic Distal Symmetric Polyneuropathy (DDSP) can affect the DM patient causing consequences as the diabetic foot and eventually amputations. The main objective of this study was to determine the prevalence of PAD and sensorial impairment in 73 type 2 DM (DM2) patients and also assess the impact of PAD on quality of life, level of physical activity and body composition. For clinical assessment it was used: the ankle-brachial index (ABI); quantitative sensorial test for tactile sensibility (ST), pain (SD), vibration (SV); Achilles tendon reflex (RA); quality of life questionnaire (SF-36); modified Baecke physical activity questionnaire and bioelectric impedance. Prevalence of PAD in the studied population was 13.7%. ABI was inversely correlated to age (p=0,03; rhô= -0,26), diabetes duration (p=0,02; rhô= -0,28) and blood pressure (p= 0,0007; rhô= -0,33). There were lower scores for physical health summary on the SF-36 in DM2 patients; however, the presence of PAD predominantly mild did not significantly impact quality of life, body composition or physical activity level assessed by questionnaire. Fourteen patients (19.2%) present bilateral and symmetrical alterations in two or more sensorial tests compatible to DPN diagnosis. Abnormalities in ST, SD and SV were present in 27.3%, 24.6% and 8.2%; respectively. There was association of results from ST abnormalities with RA and mainly with SD, suggesting the importance of 10g monofilament use in DM2 routine assessment. In conclusion, the prevalence of PAD in subclinical DM2 was slightly higher compared to the general population and in agreement to previously published data in DM patients. The PAD severity was predominantly mild and still without repercussion on quality of life and body composition. Our study demonstrated a significant prevalence of both PAD and DPN in DM2 without previous diagnosis of these complications and indicates the necessity of early preventive and therapeutic interventions for this population